دور الإدارة البيئية في تحسين الأداء المالي في المؤسسة الإقتصادية - مختار عتيقة (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2023)
الملخص: تهدف هذه الد ا رسة إلى التعرف على مفاهيم الإدارة البيئية ودورها في تحسين الأداء البيئ ي وعلى واقع حماية البيئة في المؤسسة الاقتصادية المطبقة لنظام الإدارة البيئية والمؤسسة ال ا رغبة في تطبيقه . ونظ ا ر لطبيعة الد ا رسة وبهدف الإجابة على مختلف التساؤلات تم الاعتماد على المنهج الوصفي في الإطار النظري وعلى المنهج التحليلي والمقابلة الشخصية لد ا رسة حالة مؤسسة الزجاج المسطح ) MFG ( المطبقة لنظام الإدارة البيئية، والبحث عن واقع نظام الإدارة البيئية في هذه المؤسسة في الجانب التطبيقي. وللإجابة عن الإشكالية توصلنا في النهاية إلى جملة من النتائج من أهمها أن نظام الإدارة البيئية بمؤسسة الزجاج المسطح تقف على الت ا زم جميع المستويات الوظيفية في المؤسسة بقيادة الإدارة العليا ، وأن الغرض من تبني ISO14001 هو تزويد المؤسسة بإطار لحماية البيئة والاستجابة للظروف البيئية المتغيرة في توازن مع الاحتياجات الاجتماعية والاقتصادية ويحدد المتطلبات التي يمكن المؤسسة من تحقيق النتائج المرجوة التي تحددها لنظام الإدارة البيئية، كما يمكن القول أن نظام الإدارة البيئية يساهم بتطوير المؤسسة الاقتصادية وذلك بتوفير معلومات للإدارة العليا على المدى الطويل من شأنها إيجاد خيا ا رت تساهم في التنمية المستدامة وذلك عن طريق تعزيز وتدعيم الأداء البيئي . كما بين ت هذه الد ا رسة أن للإدارة البيئية دور فعال في تحسين الأداء البيئي بالمؤسسة الاقتصادية، وأن هذا ا رجع لمستوى تطبيق أدوات نظام الإدارة البيئية. الكلمات المفتاحية: الإدارة البيئية، ISO14001 ، الأداء البيئي، التنمية المستدامة، المؤسسة الاقتصادية.Summary: This study aims to identify the concepts of environmental management and its role in improving environmental performance and the reality of environmental protection in the economic institution applying the environmental management system and the institution wishing to apply it. Given the nature of the study and with the aim of answering various questions, we relied on the descriptive approach in the theoretical framework and on the analytical approach and personal interviews to study the case of the Flat Glass Foundation (MFG) implementing the environmental management system, and to search for the reality of the environmental management system in this institution in the applied aspect. To answer the problem, we ultimately reached a number of results, the most important of which is that the environmental management system of the Flat Glass Corporation stands for the commitment of all functional levels in the organization to the leadership of senior management, and that the purpose of adopting ISO14001 is to provide the organization with a framework for protecting the environment and responding to changing environmental conditions in balance with needs. It determines the social and economic requirements that enable the institution to achieve the desired results that it sets for the environmental management system. It can also be said that the environmental management system contributes to the development of the economic institution by providing information to senior management in the long term that will create options that contribute to sustainable development by enhancing and strengthening performance. Environmental. This study also showed that environmental management has an effective role in improving the environmental performance of an economic institution, and that this is due to the level of application of environmental management system tools. key words: Environmental management, ISO14001, environmental performance, sustainable development, economic enterprise .
الأربعاء - ولاية البليدة (MFG) دراسة حالة مؤسسة الزجاج المسطح
Keywords: الإدارة البيئية; ISO14001; الأداء البيئي; التنمية المستدامة; المؤسسة الإقتصادية